Ki-67 cell proliferation in familial and in esporadic unilateral retinoblastoma: case report - Bonanomi,Maria Teresa Brizzi Chizzotti (2007)
PURPOSE: Ki-67 is a nuclear protein that is expressed at all phases of the cell cycle except the resting phase. This study is a clinicopathologic observational case report that aims to report on the cell proliferation rates, as measured by the Ki-67 antigen, in two enucleated retinoblastoma eyes. METHODS: One unilateral familial (mother with unilateral disease - patient 1) and one unilateral sporadic retinoblastoma (patient 2) patients were submitted to enucleation without previous treatment. The tumor cell proliferation rate was assessed by the Ki-67 antigen labeling index (stained cells / 100 cells) in five different fields of the tumor. RESULTS: Patient 1 was 23 months old and the tumor was exophytic with associated neovascularization of the iris; patient 2 was 6 years old and the tumor was endophytic with coarse vitreous seeds. Both enucleated eyes presented optic nerve with free surgical margins. Positive Ki-67 cell index in patient 1 varied from 75 to 90 (MD ± SD: 79.5 ± 6.61) and in patient 2 from 38 to 60 (MD ± SD: 46.6 ± 8.2). CONCLUSIONS: The familial retinoblastoma, besides the earlier age presentation, showed 45.8% more Ki-67 positive cells than the same stage sporadic one. This proliferation rate may explain the earlier presentation age of the tumor in the inherited disease.